Mercenary Swedes : French subsidies to Sweden 1631-1796 - Norrhem, Svante, 1962- (Nordic Academic Press, 2019)
Four hundred years ago, France persuaded Sweden to fight on its side against Germany in the war between Protestant and Catholic states. Rather than some lofty purpose, what convinced Sweden was money. Under the 1631 agreement, Sweden received French subsidies to the tune of 400,000 riksdaler a year for five years. This was only the first in a long line of subsidy agreements between the countries. Sweden enjoyed French largesse for no fewer than 166 years. In this wide-ranging international study, Svante Norrhem traces the patterns of cooperation between the two countries. With his unique command of the archival material, he discusses the reasons for the agreements and the mutual dependency that resulted.